The Morphological Structure of Igbo Male Nicknames - Onu , John Odo; Essien, Inoma Nsima George (International Journal of Arts, Languages, Linguistics and Literary Studies, 2024)
The study examines the morphological structure of Igbo male nicknames. It is aimed at analysing the morphology of Igbo male nicknames selected from elders and name bearers through snowballing and simple face to face interviews. Participant observation was employed from naturally occurring interactions in public and private spheres over a period of six months. The study applied descriptive research design largely informed by qualitative approach. The study employed descriptive linguistic theory in order to analyse and provide adequate descriptions of the identified morphological patterns of selected nicknames as they appear in the Igbo language. The findings of the study revealed that, Igbo nicknames have references and sense relations which are denotative and connotative and these make them meaningful. It was also revealed that Igbo nicknames have a morphological structure where prefixes and suffixes added to roots or stems alter their meanings. They are de-nominal, de-verbal and de-adjectival. They display long, and short clauses and a proverbial structure. The study revealed that conventions regarding nickname coinage and usage are intimately connected to the gender of bearers and users.